Identification of galactofuranose antigens such as galactomannoproteins and fungal-type galactomannan from the yellow koji fungus (Aspergillus oryzae) - Kadooka, Chihiro; Tanaka, Yutaka; Hira, Daisuke; Maruyama, Jun-ichi; Goto, Masatoshi; Oka, Takuji (Frontiers in Microbiology, 2023)
Filamentous fungi belonging to the genus Aspergillus are known to possess galactomannan in their cell walls. Galactomannan is highly antigenic to humans and has been reported to be involved in the pathogenicity of pathogenic filamentous fungi, such as A. fumigatus, and in immune responses. In this study, we aimed to confirm the presence of D-galactofuranose-containing glycans and to clarify the biosynthesis of D-galactofuranose-containing glycans in A. oryzae, a yellow koji fungus. We found that the galactofuranose antigen is also present in A. oryzae. Deletion of ugmA, which encodes UDP-galactopyranose mutase in A. oryzae, suppressed mycelial elongation, suggesting that D-galactofuranose-containing glycans play an important role in cell wall integrity in A. oryzae. Proton nuclear magnetic resonance spectrometry revealed that the galactofuranose-containing sugar chain was deficient and that core mannan backbone structures were present in ΔugmA A. oryzae, indicating the presence of fungal-type galactomannan in the cell wall fraction of A. oryzae. The findings of this study provide new insights into the cell wall structure of A. oryzae, which is essential for the production of fermented foods in Japan.